IMPACT OF AN EDUCATION PROGRAMME FOR HEALTH PROFESSIONALS ON SUPPORTING PREFERRED PRIORITIES FOR CARE DISCUSSIONS WITH PATIENTS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Powell, Paula; Cummins, Janet; Gallagher, Lisa; Joyce, Anne-Marie
Abstract : Background: This poster describes an audit conducted by the Community Integrated Advance Care Planning Team for St Helens and Knowsley of documentation by patients of their Preferred Priorities for Care and the impact of this on their place of death. Aim: For St Helens and Knowsley Community Services advance care planning has been a priority since 2009 when a facilitator came into post to support this. A number of education initiatives across both areas have focused on giving health professionals the skills and confidence to support patients in making decisions about their care and documenting them. A robust audit trail has allowed the team to track the Preferred Priorities for Care (PPC) document that is used locally and collate the data on patient's place of death in comparison to their preference. Results: 1007 PPC documents have been completed to date with 659 deaths so far. 1 (0.1%) patient chose hospital as their preferred place of dying. 30 (3%)chose hospice as their first choice 96.9% home or care home (usual place of residence) The audit has shown that 88% of patients who completed a PPC achieved their preference for place of dying which is significantly above the 40% home/care home deaths in the locality. The audit has also provided data on which health professionals and settings are completing PPCs and where training can be targeted for the future. Conclusion: Supporting (through education) health professionals to make advance care plans with patients can have a significant impact on a patient's place of care at the end of their life.